2018
DOI: 10.1055/s-0038-1637018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Rehabilitation in Total and Unicompartmental Knee Arthroplasty

Abstract: This study evaluated the use of telerehabilitation during the postoperative period for patients who underwent total knee arthroplasty (TKA) or unicompartmental knee arthroplasty (UKA). Specifically, this study evaluated the following: (1) patient compliance and adherence to the program, (2) time spent performing physical therapy exercises, (3) the usability of the virtual rehabilitation platform, and (4) clinical outcome scores in a selected primary knee arthroplasty cohort. A total of 157 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 30 publications
5
59
0
1
Order By: Relevance
“…Orthopedic remote rehabilitation leads to reduced costs for the national health system. As already proven in other medical fields [34], decreased costs are related to the reduction of transports, hospitalizations, and readmissions [6,17,[22][23][24]27,30,33,38]. It is assumed that for patients living more than 30 km away from the rehabilitation center, savings are around 230 dollars [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopedic remote rehabilitation leads to reduced costs for the national health system. As already proven in other medical fields [34], decreased costs are related to the reduction of transports, hospitalizations, and readmissions [6,17,[22][23][24]27,30,33,38]. It is assumed that for patients living more than 30 km away from the rehabilitation center, savings are around 230 dollars [34].…”
Section: Discussionmentioning
confidence: 99%
“…Details about number of patients, study design, remote virtual rehabilitation technology, and follow-up are reported in Table 1. 13 Feasibility study VR/AR 0 Chughtai 2019, Ohio [17] 157 Non-randomized trial VR 1 month The majority of the studies analyzed telerehabilitation (56%), 28% analyzed VR and AR, and 16% analyzed gamification.…”
Section: Studies and Patients Characteristicsmentioning
confidence: 99%
“…Of the 13 publications, 7 were ineligible as they did not clearly commence more than three months after a total knee replacement [22][23][24][25][26][27][28][29] . Two publications were not randomised controlled trials 30,31 . One randomised controlled trial included the WOMAC subscale as a pain measure in the author's manuscript 20 but this was not included in the nal edition 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Virtual rehabilitation systems are intended to meet the needs of the mechanical part of the motor skills recovery treatment [14]. Initially these rehabilitation systems were focused only on being a guide of movements, since they showed an avatar that carried out the example of the movement to be carried out.…”
Section: Introductionmentioning
confidence: 99%